RANCANG BANGUN SISTEM INFORMASI PENJUALAN TOKO BUDI LUHUR BERBASIS WEB DENGAN INTEGRASI PEMBAYARAN ONLINE - ilham rusydi abdullah; Muhammat Rasid Ridho (Universitas Putera Batam, 2025)
In era of highly dynamic information system. The use of computers has become the primary tool for data management, which is now a crucial necessity. Budi Luhur Store is a retail business that sells various necessities such as groceries, personal hygiene products, and household items. Currently, the sales system at Budi Luhur Store is still manual system, using book for record-keeping. The recorded inventory levels often do not match the actual stock sold, making it difficult to determine total payment and income, which can lead to errors. Payments are only made through conventional transactions. The main objective of this research is to implement a web-based sales information system integrated with online payment at Budi Luhur Store, which can be utilized by both the store owner and customer. Extreme Programming (XP) is one of the well-known processes within the Agile methodology. The result of the research conducted by the author indicate that implementing an automated web-based system accessible across various devices has been successful. Multiple online payment methods are available, making it easier for customers to complete transactions. The conclusion is that the implementation of a web-based sales information system at Budi Luhur Store has provided easiness in business operations. The integration of online payment methods has also enhanced transaction convenience for customers.